Mapping of hydrothermal alteration in Mount Berecha area of main Ethiopian Rift using hyperspectral data - Oluwadebi, Ayomiposi G. (2020)
Airborne Imaging Spectroradiometer for Applications (AISA) Hawk data was used to identify and map hydrothermal alteration mineralogy in Mount Berecha area of Main Ethiopian Rift valley. The Airborne image mapping was coupled with laboratory analysis involving reflectance spectroscopic measurements with the use of ASD FieldSpec for mineral and rock samples. The study was based in the shortwave infrared wavelength (SWIR) region. Laboratory spectra acquired from field data analysis served as guide in selecting image endmembers which were used as input in Spectral Angle Mapper (SAM) classification for mineral mapping. SWIR spectroscopy was able to detect the main very fine grained mineral assemblages which occur in the study area, including kaolinite, halloysite, opal, montmorillonite, nontronite, calcite, K-alunite, palygorskite, MgChlorite, zoisite, illite and mixtures of these minerals. SAM classification algorithm gives the overall classification of the alteration minerals of Berecha area and was used to generate the surficial mineral map of the study area. Berecha alteration is related to low sulfidation system and the most widespread alteration effects are represented essentially in advanced argillic alteration assemblage consisting mainly of kaolinite + opal + smectite + alunite which is likely of steam heated origin.